Simulated annealing optimization and experiments of a five-bar aerating mechanism for vertically aerating on salt-affected lands - Zhang, Yifu; Li, Hongwen; Zhang, Ruihong; Ding, Shuang (International Journal of Agricultural and Biological Engineering, 2021)
Current agronomic improving treatments for soil salinization are faced with challenges of heavy workload, high cost, etc., which may seriously restrict agricultural productivity and sustainability on a large scale. Aerator has been applied to loosen soil and enhance soil permeability. In this research, aiming to realize vertically aerating, an aerator with a five-bar aerating mechanism was proposed to improve the aerating performance for saline-alkali land. The five-bar structure of aerating mechanism was designed based on analysis of the aerator on saline-alkali land. The kinematic model was established to describe the aerating process, and the key parameters of the aerating mechanism were obtained by satisfying the motion trajectory conditions. Subsequently, the related parameters were optimized by a simulated annealing method. Furthermore, numerical modeling was simulated to verify the perpendicularity performance after aerating head hitting into the soil. The simulation results indicated that the optimized five-bar aerating mechanism could decrease swinging extreme value by 24% compared with the initial parameters. Finally, the physical prototype of the aerator was tested in the field and performed as expected, producing <7 mm depth tolerances and <3.3° angle tolerances, which met the design requirement. Keywords: salinization, five-bar aerating mechanism, vertically aerating, simulated annealing method, computer simulation DOI: 10.25165/j.ijabe.20211401.5322 Citation: Zhang Y F, Li H W, Zhang R H, Ding S. Simulated annealing optimization and experiments of a five-bar aerating mechanism for vertically aerating on salt-affected lands. Int J Agric & Biol Eng, 2021; 14(1): 151–156.